2016
DOI: 10.1002/jsfa.7872
|View full text |Cite
|
Sign up to set email alerts
|

Rapid biodegradation of aflatoxin B1 by metabolites of Fusarium sp. WCQ3361 with broad working temperature range and excellent thermostability

Abstract: Fusarium sp. WCQ3361 is the first reported AFB1 degradation fungus belonging to the genus Fusarium with broad working temperature range, excellent thermostability and high activity, which provides a potential highly useful solution for dealing with AFB1 contamination in the human diet and animal feed. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…However, Fusarium sp. WCQ3361 metabolites displayed excellent thermostability, since temperature change (0–90 °C) did not significantly affect the AFB 1 degradation activity [ 23 ]. Similarly, the culture supernatant of DY3108 showed excellent thermostability, since the degradation rate increased with increasing temperature up to 80 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Fusarium sp. WCQ3361 metabolites displayed excellent thermostability, since temperature change (0–90 °C) did not significantly affect the AFB 1 degradation activity [ 23 ]. Similarly, the culture supernatant of DY3108 showed excellent thermostability, since the degradation rate increased with increasing temperature up to 80 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Kavitha et al [ 34 ] isolated an antifungal protein with robust thermal stability from Bacillus polymyxa strain VLB16, which still maintained activity after sterilization (15 min at 121 °C). In addition, Wang et al [ 23 ] found that the metabolites of Fusarium sp. WCQ3361 exhibited high thermal stability and 99.40% residual activity to degrade AFB 1 was retained even after boiling for 10 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few of these methods conform to the Food and Agriculture Organization’s (FAO) requirement that the reduction of AFB1 is achieved while maintaining the nutritional value without residual toxicity or modifying the food or feed properties [6,7]. Biological degradation has proven to be an efficient, safe, and feasible method for AFB1 removal because its raw materials are non-polluting, highly specific, mild, and environmentally friendly; this process also discourages toxin regeneration [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas spp. Stenotrophomonas spp., Arthrobacter spp., and members of the family Flavobacteriaceae were shown in vitro to produce aflatoxin-degrading enzymes causing a significant reduction (>90%) in the levels of AFB1, AFM1 and/or AFB2 [217][218][219][220]. However, for these microorganisms to be effective in vivo, they have to colonize the intestinal tract and express sufficient levels of the aflatoxin-degrading enzymes.…”
Section: Reducing the Risk By Interfering With The Bioavailability Ofmentioning
confidence: 99%